Case report: POLE (P286R) mutation in a case of recurrent intestinal leakage and its treatment - Xiang, Dang; Fu, Gongbo; Chen, Yitian; Chu, Xiaoyuan (Frontiers in Oncology, 2023)
In recent years, although new drugs and molecular markers have been used to treat metastatic colorectal cancer, there has been little progress in the immunotherapy of advanced colon cancer. The development of sequencing and multiomics technology helps us classify patients more accurately, and then find patients who may benefit from immunotherapy. The development of this advanced technology and immunotherapy based on new targets may herald a new era in the treatment of metastatic colorectal cancer. It is well known that colorectal cancer with dmmr/msi-h phenotype is sensitive to immunetherapy, yet POLE mutation is the MSS phenotype in colorectal tumors but also effective for immunotherapy. This paper described a case of recurrent intestinal leakage that required multiple surgical procedures. A high-grade colon adenocarcinoma was identified on surgical histopathology after 18 months, and bevacizumab combined with oxaliplatin and capecitabine proved ineffective against this cancer. An analysis of gene expression indicated that POLE (P286R) mutation, TMB 119.333 mutation per 100 MB, and immune checkpoint inhibitor treatment had a significant impact. This case reminds us that the existence of malignant tumors should be considered for patients with repeated intestinal leakage, and emphasizes the importance of gene detection in the treatment of malignant tumors and the significance of POLE mutations in colorectal cancer.